Payment card industry data security standard handbook - Virtue, Timothy M., 1975- (Hoboken, N.J. : John Wiley & Sons, 2009)
The recent plethora of information security and payment card data breaches has created a tremendous amount of problems for consumers, retailers, financial institutions and service providers. Payment Card Industry Data Security Standard Handbook addresses the payment card industry standard that includes requirements for security management, policies, procedures, network architecture, software design, and any other critical protective measures. It is an all-inclusive resource for payment card industry compliance, providing CIOs, IT managers, controllers, and accounts payable/receivable managers.
Payment Card Industry Data Security Standard Handbook; CONTENTS; INTRODUCTION; Part I: The Fundamentals; Chapter 1: PCI Fundamentals; Chapter 2: Security 101; Part II: PCI Breakdown (Control Objectives and Associated Standards); Chapter 3: Build and Maintain a Secure Network; Chapter 4: Protect Cardholder Data; Chapter 5: Maintain a Vulnerability Management Program; Chapter 6: Implement Strong Access Control Measures; Chapter 7: Regularly Monitor and Test Networks; Chapter 8: Maintain an Information Security Policy; Part III: Strategy and Operations; Chapter 9: Assessment and Remediation.
Includes bibliographical references (pages 201-208) and index.
Print version record.
John Wiley and Sons
Keywords: Credit cards -- Security measures; Data protection; x -- Mesures; Protection de l'information (Informatique); BUSINESS & ECONOMICS -- Banks & Banking; Data protection